2018
DOI: 10.7759/cureus.2995
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity in Parkinson’s Disease: A Mini-Review

Abstract: This article will discuss the effects of physical activity in patients with Parkinson’s disease. Presently, the motor and non-motor symptoms are difficult to treat with the current treatment of Parkinson's; therefore, as an adjuvant to the current treatment physical activity, has been recommended. Physical activity has been known to improve many symptoms in patients with Parkinson's disease. Some of these symptoms include the physical capacities, physical and cognitive functional capacities. Physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…There is now an increasing body of clinical evidence suggesting that physical exercise is a beneficial, cost-effective, and low-risk intervention for patients with PD. According to Fayyaz et al (2018), optimally prescribed physical exercise programs may modulate neurophysiological processes possibly slowing down PD symptoms, especially for patients with moderate cognitive and physical impairment. PA has been shown to attenuate dopaminergic neuron damage and reduce cellular inflammation and oxidative stress (Nardello et al, 2017), thus playing a pivotal role in non-pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There is now an increasing body of clinical evidence suggesting that physical exercise is a beneficial, cost-effective, and low-risk intervention for patients with PD. According to Fayyaz et al (2018), optimally prescribed physical exercise programs may modulate neurophysiological processes possibly slowing down PD symptoms, especially for patients with moderate cognitive and physical impairment. PA has been shown to attenuate dopaminergic neuron damage and reduce cellular inflammation and oxidative stress (Nardello et al, 2017), thus playing a pivotal role in non-pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It has a positive effect on physical capacity and physical/cognitive function, including improvements in gait, mobility, posture, and balance [ 1 ]. In addition, several meta-analyses and systematic reviews have concluded that exercise and physical therapy improve many Parkinson disease–specific motor and nonmotor symptoms [ 2 - 6 ]. Importantly, there are several lines of evidence, using rodent Parkinson disease models and in humans with Parkinson disease, that suggest a possible disease-modifying effect of exercise on Parkinson disease [ 7 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research on the efficacy of physical exercise in treatment of other brain disorders is still in its infancy and therefore not part of the standard care. Although several studies have investigated the effect of physical exercise in different chronic brain disorders such as Alzheimer's disease (AD) [17,18], multiple sclerosis (MS) [19][20][21], Parkinson's disease (PD) [22,23], Schizophrenia (Sz) [24,25] and unipolar depression (UD) [26][27][28], results and mainly recommendations for clinical practice have been highly diverse [29]. As a consequence, current evidence for efficacy of exercise therapy is still disputed and exercise is not part of the regular care offer for patients with aforementioned disorders in most countries.…”
Section: Introductionmentioning
confidence: 99%